Sustainable Development, Education and Learning: The Challenge of Inclusive, Quality Education for All - Fujii, Hiroki (Nordic Journal of Comparative and International Education (NJCIE), 2024)
Review of the book authored by Victoria W. Thoresen, Agenda Publishing, 2023